Synthesis, 68Ga-Radiolabeling, and Preliminary In Vivo Assessment of a Depsipeptide-Derived Compound as a Potential PET/CT Infection Imaging Agent. (28th January 2015) - Mokaleng, Botshelo B.; Ebenhan, Thomas; Ramesh, Suhas; Govender, Thavendran; Kruger, Hendrik G.; Parboosing, Raveen; Hazari, Puja P.; Mishra, Anil K.; Marjanovic-Painter, Biljana; Zeevaart, Jan R.; Sathekge, Mike M.
Abstract : Noninvasive imaging is a powerful tool for early diagnosis and monitoring of various disease processes, such as infections. An alarming shortage of infection-selective radiopharmaceuticals exists for overcoming the diagnostic limitations with unspecific tracers such as 67/68 Ga-citrate or 18 F-FDG. We report here TBIA101, an antimicrobial peptide derivative that was conjugated to DOTA and radiolabeled with 68 Ga for a subsequent in vitro assessment and in vivo infection imaging using Escherichia coli -bearing mice by targeting bacterial lipopolysaccharides with PET/CT. Following DOTA-conjugation, the compound was verified for its cytotoxic and bacterial binding behaviour and compound stability, followed by 68 Gallium-radiolabeling. µ PET/CT using 68 Ga-DOTA-TBIA101 was employed to detect muscular E. coli -infection in BALB/c mice, as warranted by the in vitro results. 68 Ga-DOTA-TBIA101-PET detected E. coli -infected muscle tissue (SUV = 1.3–2.4) > noninfected thighs ( P = 0.322 ) > forearm muscles ( P = 0.092 ) > background ( P = 0.021 ) in the same animal. Normalization of the infected thigh muscle to reference tissue showed a ratio of 3.0 ± 0.8 and a ratio of 2.3 ± 0.6 compared to the identical healthy tissue. The majority of the activity was cleared by renal excretion. The latter findings warrant further preclinical imaging studies of greater depth, as the DOTA-conjugation did not compromise the TBIA101's capacity as targeting vector.